Development and validation of a multi-institutional nomogram of outcomes for PSMA-PET-based salvage radiotherapy for recurrent prostate cancer - Zamboglou, Constantinos; Körber, Stefan A.; Debus, Jürgen (JAMA network open, 2023)
Prostate-specific antigen membrane positron-emission tomography (PSMA-PET) is increasingly used to guide salvage radiotherapy (sRT) after radical prostatectomy for patients with recurrent or persistent prostate cancer. To develop and validate a nomogram for prediction of freedom from biochemical failure (FFBF) after PSMA-PET–based sRT.
Gesehen am 15.11.2023